Brain Multimodality Monitoring: A New Tool in Neurocritical Care of Comatose Patients - Nudrat Tasneem; Edgar A. Samaniego; Connie Pieper; Enrique C. Leira; Harold P. Adams; David Hasan; Santiago Ortega-Gutierrez (Critical Care Research and Practice)
Neurocritical care patients are at risk of developing secondary brain injury from inflammation, ischemia, and edema that follows the primary insult. Recognizing clinical deterioration due to secondary injury is frequently challenging in comatose patients. Multimodality monitoring (MMM) encompasses various tools to monitor cerebral metabolism, perfusion, and oxygenation aimed at detecting these changes to help modify therapies before irreversible injury sets in. These tools include intracranial pressure (ICP) monitors, transcranial Doppler (TCD), Hemedex™ (thermal diffusion probe used to measure regional cerebral blood flow), microdialysis catheter (used to measure cerebral metabolism), Licox™ (probe used to measure regional brain tissue oxygen tension), and continuous electroencephalography. Although further research is needed to demonstrate their impact on improving clinical outcomes, their contribution to illuminate the black box of the brain in comatose patients is indisputable. In this review, we further elaborate on commonly used MMM parameters, tools used to measure them, and the indications for monitoring per current consensus guidelines.